Rapid assessment of myco-heterotrophic plants diversity at Sungai Rawog conservation area - Ahmad Asnawi Mus; Siti Fatimah Md.-Isa; Mohd Gan Abdul Rashid; Franey Joseph Chong; Edward Entalai Besi; Debbie anak Sandin (Sabah Forestry Department, 2024)
Myco-heterotrophic species are plants that lack photosynthetic pigments and relies on symbiotic relationship with fungi to survive. However, little attention has been given to the diversity of myco-heterotrophic species from Sabah, especially at Sungai Rawog Conservation Area. Thus, this study is a preliminary effort to accumulate the undiscovered myco-heterotrophic species diversity in Sabah. A total of seven trails namely Trail 1, 2, 3, 4, 7, 8 and Nepenthes trail were explored in four days. Findings were also compared to previous sampling that were done in Borneo. A total of three myco-heterotrophic species confined to three genera were collected from only Trail 3, 4 and 7. The myco-heterotrophic orchid Lecanorchis multiflora were found in Trail 3 and 4. Meanwhile, Gymnosiphon aphyllus was abundant only in trail 4. On the other hand, Epirixanthes confusa was only restricted to trail 7. The preliminary finding obtained from this study suggested that an extensive study is required to inventory the myco-heterotrophic species in the diverse forest types available in Sabah.